G45 The Diagnosis of Urinary Tract Infection in Young Children (DUTY) Study: The Development of a Clinical Algorithm to Improve the Recognition of Urinary Tract Infection (UTI) in Pre-School Children Presenting to Primary Care. (4th June 2013) - Hay, AD; Hood, K; Sterne, J; Dudley, J; Voort, J van der; Howe, R; Wooton, M; MacGowan, A; Delaney, B; Little, P; O'Brien, K; Thomas-Jones, E; et al.
Abstract : Aim: To develop a clinical algorithm based on symptoms, signs and urine dipstick results to assist the identification of children who require urine sampling, antibiotic treatment and/or laboratory analysis. Methods: We conducted a diagnostic cohort study of children <5 years presenting acutely (≤28 days) unwell to primary care in the UK. We collected detailed information on the presence/absence and severity of presenting symptoms and signs, as well as socio-demographic and past medical history data. Urine was sampled by clean catch (preferred) or nappy pad, 'dipsticked' and sent to (i) the local NHS laboratory (the priority sample) and (ii) a reference laboratory. Blind to children's clinical symptoms and signs, the NHS and reference laboratories processed urine samples according to their standard operating procedures. Results (preliminary): 7, 163 children were recruited with NHS and research urine sample results available for 6, 328 (88%) and 5, 257 (73%) respectively. Of the 5, 017 children without missing data and with urine results from both laboratories: mean age was 2.2 years (s.d. = 1.4); 49% were male; 54% urines via clean catch, 45% via nappy pads and 1% via bag. UTI rates were 2.8% and 3% from clean catch and pad samples respectively. Among clean catch samples, the following were independently associated with UTI: history of UTI; parental report of smelly urine; pain/crying while passing urine; clinician's global impression of illness severity; and on dipstick: nitrites, leukocytes and blood (area under the ROC = 0.87 (95% CI 0.82 to 0.92). Among the nappy pad samples, the factors were: female gender; age; smelly urine; darker urine; and on dipstick: nitrites, leukocytes and blood (AUROC = 0.78 (0.72 to 0.83)). Conclusions: Symptoms, signs and dipstick testing have diagnostic utility for UTI. These results will be developed into an algorithm to help clinicians select which should have: a urine sample obtained; a sample sent for laboratory culture and receive immediate antibiotic treatment.